Postoperative Complications of Laparoscopic Total Gastrectomy versus Open Total Gastrectomy for Gastric Cancer in a Meta-Analysis of High-Quality Case-Controlled Studies - Mikito Inokuchi; Sho Otsuki; Norihito Ogawa; Toshiro Tanioka; Keisuke Okuno; Kentaro Gokita; Tatsuyuki Kawano; Kazuyuki Kojima (Gastroenterology Research and Practice)
Background. Some meta-analyses of case-controlled studies (CCSs) have shown that laparoscopic or laparoscopy-assisted total gastrectomy (LTG) had some short-term advantages over open total gastrectomy (OTG). However, postoperative complications differed somewhat among the meta-analyses, and some CCSs included in the meta-analyses had mismatched factors between LTG and OTG. Methods. CCSs comparing postoperative complications between LTG and OTG were identified in PubMed and Embase. Studies matched for patients’ status, tumor stage, and the extents of lymph-node dissection were included. Outcomes of interest, such as anastomotic, other intra-abdominal, wound, and pulmonary complications, were evaluated in a meta-analysis performed using Review Manager version 5.3 software. Result. This meta-analysis included a total of 2,560 patients (LTG, 1,073 patients; OTG, 1,487 patients) from 15 CCSs. Wound complications were significantly less frequent in LTG than in OTG (n = 2,430; odds ratio [OR] 0.30, 95% confidence interval [CI] 0.29–0.85, P=0.01, I2 = 0%, and OR 0.46, 95% CI 0.17–0.52, P<0.0001, I2 = 0%). However, the incidence of anastomotic complications was slightly but not significantly higher in LTG than in OTG (n = 2,560; OR 1.44, 95% CI 0.96–2.16, P=0.08, I2 = 0%). Conclusion. LTG was associated with a lower incidence of wound-related postoperative complications than was OTG in this meta-analysis of CCSs; however, some concern remains about anastomotic problems associated with LTG.